Giving a Chance to the Green Energy to Save our Planet Future - Majid, Layth Hazim (Journal of Economic Development, Environment and People, 2019)
The present paper focuses on analysing the effects of using green energy on achieving sustainable development. The competitive advantages and emphasised here and sustained to push finding farther ways to transform the world into a green planet as it was at its beginnings. Under smart strategies implemented reasonably the green energy encourages smart investments and builds a better world for people and companies benefit.